(untitled) (Research, Society and Development, 2020)
The deposition of dead coverings in the planting system can directly affect vegetative components and vegetable production coefficients. The radish being a small plant and easy to produce and commercialize, it has few more organic production alternatives, with this the present work sought to evaluate the growth and production coefficients index of Raphanus sativus L. grown in different types of mulch vegetable. The work was developed in a protected environment with a 50% black screen, at the Auroras Seedling Production Unit (UPMA) at the Auroras Campus at the University of International Integration of Afro-Brazilian Lusophony (UNILAB), Redenção, Ceará, in the Maciço region. Baturité. The experimental design was randomized blocks (DBC), with treatments arranged in four blocks and five repetitions, totaling 20 experimental units. There were four treatments, T1-rice straw, T2-carnauba bagana, T3-mulching and T4-control. The variables analyzed in growth were stem diameter, leaf area, number of leaves and plant height and in the production period were root length, root diameter and root mass. The rsults were subjected to analysis of variance and the means compared by Tukey’s test with p <0.05, if the program SISVAR 5.0 was used and later correlated with Pearson with the program EXCEL 2016 to adsorb the results of research A carnaúba bagana and “mulching” stood out in relation to the soil with other coverings such as the materials that provided better values of production components.